EXTENT OF CREDIT FINANCING BY COMMERCIAL BANKS TO AGRIBUSINESSES IN KENYA - Benjamin Owuor Ombok; David Odhiambo Oima; Moses Oginda (European Scientific Journal, ESJ, 2014)
Financing in the Agribusiness sector has been difficult due to perceived and unmanaged sectoral risk factors although it contributes to employment by up to 53% in a majority of poor and developing countries, 60% in South Saharan Africa; and up to 80% to the Kenyan population. Despite the commercial banks’ application of credit risk mitigation mechanisms, there is little empirical evidence on the use of the forward integration credit risk mitigants on the performance of the agribusiness firms. The purpose of this study was to determine the extent to which the commercial banks provide credits to agribusiness firms. Specifically the study sought to ascertain the extent to which the commercial banks grant credit financing to the agribusiness enterprises in Nyanza region and determine the agribusiness borrowers’ opinion on commercial banks’ application of forward integration credit risk mitigation mechanisms in granting credits to them. This study takes a descriptive research design. The target population comprised 183 agribusiness firms in operation for the period 2003 to 2012. Stratified random sampling was used to select a sample size of 45 agribusiness managers. Both primary and secondary data were used. The study findings reveal that the commercial banks grant an average of 4.98% credit funding to the agribusiness capital level, 12.40% to owner equity and 4.38% share of credit extended to the agribusiness sector. Borrowers’ opinion reveal that the commercial banks highly consider the credit volume determinants in extending credits to the agribusinesses at a mean of 2.2372.